До питання про підвищення ефективності глибокого свердління гвинтовими свердлами за рахунок керування адгезіонної складовою сили тертя - Маршуба, В'ячеслав Павлович; Чернякова, О. В. (Українська інженерно-педагогічна академія, 2013)
The article examines on sacred to research of increasing of efficiency of processing deep holes by spiral drills on the base of existent developments in various directions. The article concerns the perfection of technological process deep holes making by spiral drills on aggregate machine-tools, automatic transfer lines and flexible productive systems.
On the question of increasing the effectiveness of deep drilling screw drill through the management adhesive component of the force of friction
Keywords: верстат агрегатний; лінії автоматичні; обробка механічна; різання; інструмент ріжучий; стружка